EFFECT OF Trichoderma sp. DOSE AND TYPE OF MANURE FERTILIZER APPLICATION ON GROWTH AND YIELD OF LONG BEANS (Vigna sinensis L) - Riyan Syah Siregar; Cik Zulia; Safruddin Safruddin (Universitas Asahan, 2018)
This research was conducted in Mentimum Street, Siumbut Baru Village, Kisaran Timur SubDistrict, Asahan Regency, North Sumatera Province. Research do from March to May 2017. This research was arranged based on Factorial Randomized Block Design with 2 treatment factors and 3 replications. The first factor of giving Trichoderma sp. With 3 levels ie: T0 = 0 g/plant, T1 = 10 g/plant, and T2 = 20 g/plant. The second factor is by giving the type of manure with 4 levels ie K0 = without manure, K1 = chicken manure, K2 = cow manure and K3 = goat manure. The results showed that giving of Trichoderma sp with dose 20 g/plant was the best treatment yielding 126,54 cm height, 4,13 branch productive branch, number of pod per plant 44,10 pod, production per plant 0,81 kg, And production per plot 6.97 kg. The best treatment on the type of manure is obtained in the type of chicken manure that produces the height of plant 127.41 cm, the number of productive branches 4,03 branches, the number of pods per plant 45.17 pods, the production per plant 0.82 kg, and the production Plot 7.00 kg. The interaction between Trichoderma sp and type of manure gave no significant difference to all observed variables.